Aberrant myelomonocytic CD56 expression predicts response to cyclosporine therapy in pediatric patients with moderate aplastic anemia - Qi, Shanshan; Du, Yu; Sun, Ming; Zhang, Lin; Chen, Zhi; Xiong, Hao (Frontiers in Pediatrics, 2023)
This study aimed to investigate the expression patterns and clinical significance of neural cell adhesion molecule-positive (CD56 + ) myelomonocytes in pediatric patients with moderate aplastic anemia (mAA). Fifty-six pediatric patients with mAA were enrolled in this study. The patients' clinical characteristics, laboratory data, and response to cyclosporine therapy were obtained. CD56 expression on bone marrow myelomonocytic cells was investigated using flow cytometry. The association between aberrant CD56 expression and cyclosporine response was evaluated by a multivariate analysis. CD56 + myelomonocytes were detected in 43% of the mAA cases. Aberrant CD56 expression was frequent on immature CD45 dim CD16 dim granulocytes and mature CD45 bright CD14 bright monocytes.Compared with patients with CD56 -myelomonocytes (CD56 -patients), patients with CD56 + myelomonocytes (CD56 + patients) were in moderate hematological condition and had a distinct bone marrow cellular composition profile, which included an increased proportion of myeloid cells and CD56 bright natural killer cells and a reduced proportion of CD4 + T cells, CD8 + T cells, and B cells. The multivariate analysis determined that CD56 + myelomonocytes were a favorable factor for achieving response at 6 months after cyclosporine therapy. There was a trend towards a lower 3-year rate of evolution to severe aplastic anemia or relapse among the CD56 + patients (8%) than the CD56 -patients (22%). In conclusion, CD56 + patients had an increased myeloid compartment and better prognosis compared with CD56 -patients. The findings demonstrated the favorable role of CD56 + myelomonocytes in aplastic anemia progression.